Genome assemblies and other genomic tools for understanding insect adaptation - Pita, Sebastián; Rico-Porras, José M; Lorite, Pedro; Mora, Pablo [UNESP] (Elsevier, 2025)
Insects, the most diverse group of animals, exhibit remarkable adaptability, playing both crucial and problematic roles in ecosystems. Recent advancements in genomic technologies, such as high-throughput sequencing, have provided unprecedented insights into the genetic foundations of insect adaptation. This review explores key methodologies, including de novo and reference-guided genome assemblies, and highlights cutting-edge technologies like second- and third-generation sequencing and hybrid techniques. The article delves into the genetic mechanisms underlying insect adaptations, focusing on structural variants. Case studies, such as the Anopheles gambiae genome assembly and the genomic research on Drosophila melanogaster, demonstrate the practical applications of these technologies in understanding pesticide resistance, climate adaptation, and other evolutionary traits. This review underscores the transformative role of genomic tools in insect research, with significant implications for pest management, agriculture, and biodiversity conservation.